A hero looks like you - Mbalia, Kwame (Marvel Press, 2025)
"Set in the world of Marvel Studios' Captain America: Brave New World, A Hero Looks Like You is a heartwarming picture book about a young boy named DJ who steps up to help Captain America, his favorite Super Hero, and discovers along the way that heroes don't always look big or strong or wear a suit. Sometimes, they might even look like him."